Status and Associated Factors of Breakfast Consumption Among Chinese Residents: A National Cross‐Sectional Study - Liu, Ming; Dong, Shujie; Li, Yifan; Liang, Shaolin; Leung, Chun Kai; Zhang, Casper J. P.; Li, Sicun; Wu, Yibo; Ming, Wai‐kit (Food science & nutrition, 2025)
ABSTRACT While the importance of breakfast for human health is widely acknowledged, there is limited understanding of the factors influencing breakfast habits among Chinese residents. We conducted a nationwide cross‐sectional survey between June 20 and August 31, 2022, analyzing weekly breakfast frequency, food categories, and associated factors to daily breakfast consumption using multivariable logistic regression, with subgroup analyses by gender and residence (urban or rural). Among 21,875 participants, 41.0% reported non‐daily breakfast consumption. Common breakfast items included staples like rice, wheat, and corn (70.5%), eggs (56.2%), dairy products (42.0%), and soy drinks (36.8%), while less frequently consumed items included meat products (26.3%), potatoes (23.4%), fresh vegetables and fruits (20.2%), and pickled vegetables (18.2%). Behavioral factors such as sleeping 6–7 h and abstaining from smoking and sugar‐sweetened beverages, along with health factors like better quality of life, family health, and higher self‐efficacy, were positively associated with daily breakfast consumption. Depression was negatively associated. Sociodemographic factors including female gender, living in southern China, and having children were positively associated, whereas rural residency, higher education levels, being a student or unemployed, and living alone were negatively associated. Subgroup analyses revealed pronounced variations in breakfast habits by residence (urban vs. rural) but fewer differences by gender. Non‐daily breakfast consumption is prevalent among Chinese residents, with multiple sociodemographic, behavioral, and health factors influencing this behavior. Region‐ and gender‐specific strategies are essential to promote healthy breakfast habits, address disparities, and encourage healthier breakfast practices across diverse subgroups. This nationwide cross‐sectional study analyzed breakfast consumption patterns among 21,875 Chinese residents. Findings revealed that 41.0% were non‐daily breakfast consumers, with common breakfast items including rice, wheat, and corn. Behavioral and health factors, such as adequate sleep and better family health, were positively associated with daily breakfast consumption, while sociodemographic disparities were evident between rural and urban residents. Tailored region‐ and gender‐specific interventions are necessary to promote healthier breakfast habits and address disparities across subgroups.